Robust Induction motor Control using Indirect Adaptive Fuzzy Synergetic Control, ISSN 1582-4594 - Medjbeur Lemya; Benaggoune Said (Journal of Electrical Engineering, Roumanie, 2015)
A new control technique of an induction motor is undertaken through a robust approach tagged synergetic control. Like the sliding mode (SMC) approach the system state trajectories are forced to evolve on a designer chosen manifold according to performance specifications. But unlike SMC, synergetic control relies on a continuous control law thus preventing unwanted chattering to occur. Fuzzy sets are used to approximate unknown system functions and system stability conditions are derived.